Academic generational differences in Chinese universities: Work preferences, research behaviors and research outputs - Yangyang Cui; Hui Guo (PLoS ONE, 2025)
Utilizing data from the 2018 Survey of Academic Profession in the Knowledge Society in China, this study examines generational divergences in work preferences and research behaviors. It further analyzes how these factors relate to the research outputs. The findings indicate that the younger generation serves as the predominant force in research production, exhibiting pronounced research preferences, dedicating more time to research activities, collaborating less, and producing the highest volume of high-impact publications (HIPs). Conversely, the older generation acts as the ‘social service representative,’ devoting more time to social service, collaborating more extensively on research, and balancing teaching and research responsibilities. The middle generation demonstrates research behaviors exhibiting intermediate associations between the older and younger cohorts. International cooperation correlates with elevated HIPs across all generations, showing the strongest association in the older generation. Research time investment positively correlates with HIPs among the younger and middle generations, while research-oriented preferences exhibit associations with HIPs among the younger and older generations. Consequently, institutions should recalibrate evaluation systems by integrating senior academics’ expertise and fostering intergenerational networks that recognize diverse contributions.